Cognitive Flexibility: Exploring Students' Critical Thinking Skills in Solving Mathematical Problems - Marzuki, Marzuki; Rusmar, Irfan; Wahyudin, Wahyudin; Juandi, Dadang (KnE Social Sciences, 2024)
Cognitive flexibility is an individual’s ability to think, and critical thinking skills in the 21st century are needed by students. This study aims to obtain a substantive theory (conjecture) that is associated with students’ critical thinking skills in solving mathematical problems. This type of research is qualitative with Grounded Theory (GT) systematic design procedures. Because the design of this research is GT, therefore, the data analysis was carried out in three stages, namely: open coding, axial coding, and selective coding with the help of NVivo 12 plus software. The participants involved were 30 students. The research guideline was in the form of a critical thinking ability test and semi-structured interview. In-depth interviews were conducted based on the results of the ability to think critically until the data was saturated. Data saturation occurred in the 5th interview. To test the reliability of critical thinking skills, categories and subcategories were carried out by two coders with a Cohen kappa value of 0.65, so that the coding was made reliable. The results obtained were hypothetical: if participants can think critically, then participants can solve problems, can provide arguments, can interpret algebraic derivative application functions, and can develop problem-solving strategies in critical thinking. Keywords: critical thinking skills, cognitive flexibility, solving mathematical problems